Effects of Dietary Multi-Strain Probiotics on Growth, Whole Body Composition and Stress Resistance of the Gangetic Catfish (Mystus Cavasius) Fry (Journal of the Bangladesh Agricultural University, 2020)
The present study was designed to evaluate the effects of dietary probiotics on growth, feed utilization, body composition, and stress resistance of the Gangetic catfish, Mystus cavasius fry. A commercially formulated feed for catfish (ACI Company Ltd.) was used as a basal diet. Three different levels (0.2, 0.4, and 0.8%) of commercial multi-strain probiotic NavioPlus was added to the basal diet to formulate three experimental diets (PB 0.2, PB0.4, PB0.8) and the basal diet was considered as control (PB0). Each diet was randomly allocated to triplicate groups of fish (mean initial weight 0.32±0.0003 g for 56 days. In general, dietary probiotics supplementations tended to improve growth performances (final body weight, percentage (%) weight gain and specific growth rate, SGR), in which significantly highest performances were found in diet group PB-0.2 followed by diet groups PB-0.4 and PB-0.8. Probiotics supplementation resulting in increased feed conversion efficiency (FCE) and protein efficiency ratio (PER) and the highest value (P 0.05) by the dietary probiotics supplementation. However, the fishes fed diet PB-0.2 and PB-0 had significantly higher and lower lipid content, respectively. In terms of salinity stress resistance, M. cavasius fry fed probiotic supplemented diet showed increased LT50 compared to the supplementation free control group. Significantly higher LT50 observed in diet group PB-0.4 followed by PB-0.8. The quadratic regression analysis of % weight gain, FCE and, LT50 revealed that the optimum level of dietary multi-strain probiotics supplementation ranged between 0.45-0.54% for M. cavasius fry, which is also in-line with the most of the measured performance parameters of fish under present experimental condition.J Bangladesh Agril Univ 18(3): 779–787, 2020https://doi.org/10.5455/JBAU.107265